Social Expenditure in New Zealand: Stochastic Projections - John Creedy; Kathleen Makale (New Zealand Government, The Treasury, 2013)
This paper presents stochastic projections for 13 categories of social spending in New Zealand over the period 2011-2061. These projections are based on detailed demographic estimates covering fertility, migration and mortality disaggregated by single year of age and gender. Distributional parameters are incorporated for all of the major variables, and are used to build up probabilistic projections for social expenditure as a share of GDP using simulation methods, following Creedy and Scobie (2005). Emphasis is placed on the considerable uncertainty involved in projecting future expenditure levels.
Keywords: E61; H50; J11; 330; Population; projections; stochastic simulation; social expenditure; fiscal costs; New Zealand; Öffentliche Sozialausgaben; Bevölkerungsprognose; Simulation; Stochastischer Prozess; Prognoseverfahren; Neuseeland